Characterization of Sustainable Graphitic Biochar from Food Waste via Microwave Irradiation Technique - Hishammuddin, Nuraqilah; Idris , Siti Shawalliah; Abd Rahman, Norazah; Abu Bakar, Noor Fitrah; Ismail, Siti Norazian; Mohamed, Alina Rayahu (International Journal of Integrated Engineering, 2025)
The significant rise in waste generation caused by global urbanization and industrialization may harm the environment, leading to climate change. According to the Solid garbage and Public Cleansing Management Corporation (SWCorp Malaysia), Malaysia generates an average of 1.17kg of garbage each day, which equates to around 3.5 million tons of food waste (FW) every year. Therefore, by transforming FW into valuable materials like graphite presents an appealing alternative due to high demand for it, particularly in energy-related applications. In this research, we introduce a new method for producing sustainable graphitic carbon from FW using microwave-assisted pyrolysis (MAP). The graphitic carbon obtained via microwave pyrolysis at power supply 1000 W at 5- and 45-minutes radiation time then underwent analysis such as X-ray diffraction (XRD), Thermogravimetric Analysis (TGA) and Fourier-Transform Infrared Spectroscopy (FTIR) to verify its structural characteristics, graphitic properties and chemical composition of graphitic carbon. The findings indicated that the microwave irradiation process successfully pyrolyzed food waste into biochar at 1000 W, 30 minutes, giving 23.9% of biochar yield with lower energy consumption (1800kJ). Whereas, the conversion to graphitic carbon from FW is about 60Gp degree of graphitisation. The new material has an excellent potential for electrical conductivity and mechanical endurance, making it appropriate for a variety of applications such as energy storage devices, catalysts, and composite materials. This investigation underscores the potential of utilizing microwave irradiation as an eco-friendly and effective method for converting food waste into valuable graphitic carbon, contributing to the advancement of a circular economy and diminishing the environmental consequences of waste disposal.